Mitigation of mismatch power loss in aged photovoltaic arrays following a comparative investigation into module rearrangement techniques. (November 2022) - Al Mansur, Ahmed; Amin, Md. Ruhul; Haq, Mohammad Asif ul; Maruf, Md. Hasan; Mottalib, Md. Mozaharul; Ashique, Ratil H.; Shihavuddin, A.S.M.
Abstract: Power degradation due to non-uniform aging is a common phenomenon in large photovoltaic array systems. Aging increases the current–voltage mismatch in the array modules that results in mismatch power loss in the array. Module rearrangement techniques based on Short Circuit Current, a conventional arrangement method, and a proposed adaptive Genetic Algorithm are investigated in this work to obtain an optimal arrangement that yields maximum output power from the aged arrays. The effectiveness of the rearrangement techniques is compared to the aged photovoltaic arrays considering four different power ratings as 400 W, 1.6 kW, 3.2 kW, and 10 kW. Simulation results show that the proposed genetic algorithm and short circuit current-based techniques reduce a maximum of 4.8% and 2.9% (average) losses compared to the conventional arrangement technique. An experimental investigation is carried out using four years aged 400 W photovoltaic array with 4 × 10, 5 × 8, 10 × 4, and 8 × 5 dimensions, where the proposed genetic algorithm-based method yields a maximum percentage of recoverable energy of 4.67% in comparison to the aged array with 8 × 5 dimension. Highlights: Determination of the severity of nonuniformly aged PV arrays in power loss. Loss minimization is achieved with the adaptive genetic algorithm-based method. Experimental validation based on four years old PV arrays. A strong correlation was established between mismatch loss and module parameters.